1995
DOI: 10.1161/01.atv.15.4.504
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Factor Pathway Inhibitor Activity in Human Plasma

Abstract: Tissue factor pathway inhibitor (TFPI), a protease inhibitor that is present in free and lipoprotein-associated forms in plasma and that also occurs as an endothelial cell-associated form, can inhibit the initial reactions of the tissue factor-mediated coagulation pathway. Although a positive correlation between plasma TFPI activity and cholesterol concentration in human plasma has been demonstrated, levels of the various forms of TFPI, ie, the LDL/VLDL-associated form, the HDL-associated form, and the free fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
10
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(12 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…TFPI activity is distributed among LDL/VLDL-associated, high density-lipoprotein (HDL)-associated, and free forms of TFPI after gel filtration of human plasma, and the free-form TFPI activity was observed to be decreased in hyperlipidemic patients [16]. At the onset of AMI in the present series of patients, the screening results of hemostasis were within normal range.…”
Section: Discussionsupporting
confidence: 45%
“…TFPI activity is distributed among LDL/VLDL-associated, high density-lipoprotein (HDL)-associated, and free forms of TFPI after gel filtration of human plasma, and the free-form TFPI activity was observed to be decreased in hyperlipidemic patients [16]. At the onset of AMI in the present series of patients, the screening results of hemostasis were within normal range.…”
Section: Discussionsupporting
confidence: 45%
“…12,13 The heparin infusion allowed us to measure the total intravascular TFPI levels, including the EC-TFPI concentration, which was 7.7 to 11.2 times greater than the preheparin free TFPI level, as previously reported. 5 As determined by comparison of preheparin and postheparin plasmas, the distribution of intravascular TFPI in the CAD patients studied consisted of Ͻ10% as the circulating preheparin free fraction (6% to 9%), 30% as the Lp-bound form (27% to 32%), and 60% as the EC-TFPI fraction (60% to 64%) regardless of the patients' dyslipidemic profiles.…”
Section: Discussionmentioning
confidence: 82%
“…The free form of TFPI inhibits tissue factor-induced coagulation more effectively than Lp-bound TFPI. 12,13 Consequently, EC-TFPI is physiologically the more important pool, mediating the major antithrombotic activity on the endothelial surface. EC-TFPI is believed to bind to heparan sulfate on the cell surface, as does lipoprotein lipase (LPL).…”
mentioning
confidence: 99%
“…Some prior reports indicated that associations exist between the TFPI level and lipid parameters, although data are conflicting. There is emerging evidence that the TFPI levels correlate with TC levels 17,24,25 and LDL-C levels, 26,27 but one study reported no relation between them. 28 Some studies have revealed an association between the TFPI levels and the HDL-C levels, 27,29 but others have not found such a relationship.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the free form in relation to the anticoagulant activity of vascular endothelial cells has been reported. 24 Lindahl et al 30 suggested that the free form of TFPI has greater anticoagulant activity relative to amidolytic activity than lipoproteinassociated TFPI. Therefore, it is noteworthy that the free form of TFPI correlated positively with HDL-C and apo A-I in the present study.…”
Section: Discussionmentioning
confidence: 99%